The Structural Shift Of Compound Complex Sentence In The Old Man And The Sea Its Translation - PRASTYANTO:, ANDRE (2012)
The aims of this research are to describe the structural shift of compound-complex sentence in The Old Man and the Sea and its translation, and to know the types of equivalence of the translation in The Old Man and the Sea and its translation. The type of this research belongs to a descriptive qualitative research, because the writer collects the data, arranges, classifies, analyzes, and concludes the result of this research. The source of the data in this research is novel The Old Man and the Sea. The data of this research are contents of novel The Old Man and the Sea which consists of structural shift of compound-complex sentences and its translations. After collecting the data, the writer analyzes them based on indication of structural shift. He finds the structural shift of declarative compound-complex sentence into declarative compound sentence. Then, he analyzes the types of equivalence of the translation and finds types of equivalence as follows; 1. coordination between formal and dynamic equivalence, 2. dynamic equivalence. The result of this research shows that there are 12 data consist of structural shift of declarative compound-complex sentence into declarative compound sentence. The writer also finds 2 types of equivalence in this analysis. They are; 6 or 50 % of data use coordination between formal and dynamic equivalence, and 6 or 50 % of data use the dynamic equivalence.